1993
DOI: 10.1242/dev.117.1.377
|View full text |Cite
|
Sign up to set email alerts
|

A mRNA localized to the vegetal cortex of Xenopus oocytes encodes a protein with a nanos-like zinc finger domain

Abstract: mRNAs concentrated in specific regions of the oocyte have been found to encode determinants that specify cell fate. We show that an intermediate filament fraction isolated from Xenopus stage VI oocytes specifically contains, in addition to Vg1 RNA, a new localized mRNA, Xcat-2. Like Vg1, Xcat-2 is found in the vegetal cortical region, is inherited by the vegetal blasomeres during development, and is degraded very early in development. Sequence analysis suggests that Xcat-2 encodes a protein that belongs to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Mouse orthologues of mitotic microtubular transcripts (Blower et al , 2007) were not differentially partitioned between Pb 2 and zygote (Supplementary Table S6) and with the sole exception (out of 19) of Lef1 ( Tcf‐1 ), neither were the putative counterparts of Xenopus oocyte polar transcripts (Supplementary Tables S7 and S8) (King et al , 2005; Jambhekar and Derisi, 2007). Some asymmetrically distributed Xenopus oocyte transcripts are enriched ∼50‐fold in the vegetal pole (Mosquera et al , 1993), but qPCR of mouse samples did not reveal enrichment of this magnitude even among mRNAs most likely to be differentially partitioned (Figure 2C). Of 53 transcripts that are abundant during mouse oocyte maturation (Wang et al , 2004), 8 (15.1%) segregated significantly, 7 of these (87.5%) preferentially into the zygote (Supplementary Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse orthologues of mitotic microtubular transcripts (Blower et al , 2007) were not differentially partitioned between Pb 2 and zygote (Supplementary Table S6) and with the sole exception (out of 19) of Lef1 ( Tcf‐1 ), neither were the putative counterparts of Xenopus oocyte polar transcripts (Supplementary Tables S7 and S8) (King et al , 2005; Jambhekar and Derisi, 2007). Some asymmetrically distributed Xenopus oocyte transcripts are enriched ∼50‐fold in the vegetal pole (Mosquera et al , 1993), but qPCR of mouse samples did not reveal enrichment of this magnitude even among mRNAs most likely to be differentially partitioned (Figure 2C). Of 53 transcripts that are abundant during mouse oocyte maturation (Wang et al , 2004), 8 (15.1%) segregated significantly, 7 of these (87.5%) preferentially into the zygote (Supplementary Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the nature of RNA-protein interactions within biological condensates is a burgeoning field, and recent work indicates that subcellular RNA localization facilitated by LLPS is critical for organismal development [84,86,134]. For example, in X. laevis oocytes, specific mRNAs must be transported to the vegetal pole for successful embryonic development [86,135]. Localization of these mRNAs occurs through interactions with RBPs and can result in the formation of RNA-protein condensates [86,136].…”
Section: Rna Corementioning
confidence: 99%
“…We also found that NANOS1 and A c c e p t e d A r t i c l e TPX2, which are associated with male reproduction, were downregulated in the pituitary and liver groups by treatment with the SS-14 DNA vaccine. NANOS1 encodes a CCHC-type zinc finger protein that is involved in regulating translation as a posttranscriptional repressor, and mutations in NANOS1 are associated with a lack of germ cells in the testis or severe oligozoospermia [37]. These results suggest that treatment of bucks with the SS-14 DNA vaccine may affect the function of germ cells in the testis and changes in protein kinase activity, which may impact the reproductive performance of bucks.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 96%